Transformational Leadership in Academic Supervision: Implications for School Development - Syahrir, Syahrir; Fandir, A.; Nurfidah, Nurfidah (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study explores the role of transformational leadership in academic supervision and its impact on school development. Using a qualitative approach with a case study design, this study focuses on principals, supervisors, and teachers involved in academic supervision. Data were obtained through in-depth interviews, observations, and literature studies. The study's results indicate that principals' transformational leadership creates a collaborative, innovative environment that supports continuous improvement in teaching quality. Principals who apply this leadership style play a role in forming a shared vision, providing positive feedback, and motivating teachers to improve teaching methods. The implications of this approach include increasing teacher competence and motivation, as well as creating a collaborative work culture in schools. This study suggests that schools implement transformational leadership in academic supervision to improve the overall quality of education